Nutritional Status and Clean Healthy Lifestyle Behavior of Santri in Islamic Boarding Schools in West Sulawesi - Najdah, Najdah; Nurbaya, Nurbaya; Yudianti, Yudianti; Irwan, Zaki; Rasmaniar, Rasmaniar; Nurlaela, Euis (Journal of Public Health for Tropical and Coastal Region, 2026)
Introduction:Islamic boarding schools, as residential educational institutions, face challenges in maintaining the health and nutritional status of students (santri), particularly concerning Clean and Healthy Living Behavior (CHLB). Santri living in densely populated environments with limited sanitation facilities are vulnerable to health issues. This study aimed to provide an overview of the nutritional status and CHLB implementation in Islamic boarding schools in West Sulawesi.Methods: This descriptive cross-sectional study was conducted from July to October 2024 among 260 santri from three Islamic boarding schools in West Sulawesi, Indonesia. The sample size was determined using the Lemeshow formula and randomly selected from the population. Data were collected through structured interviews and analyzed using descriptive statistical tests.Results: The results showed that 81.2% of the santri had a normal nutritional status, while 6.5% were undernourished, 8.8% were overweight, and 3.5% were obese. Bathing twice a day had the highest compliance rate (mean 4.75), while not sharing personal items had the lowest compliance rate (mean 2.96).Conclusion: Although most santri have a normal nutritional status, some groups still experience undernutrition, obesity, and risky health behaviors. Continuous interventions in the form of nutrition education and CHLB improvement programs are necessary to raise awareness and promote healthy behaviors in Islamic boarding schools.